Developmental Easing of Short-Term Depression in “Winner” Climbing Fibers - Pätz, Christina; Brachtendorf, Simone; Eilers, Jens (Frontiers in Cellular Neuroscience, 2019)
The postnatal development of cerebellar climbing fiber (CF) to Purkinje neuron (PN) synapses is characterized by a substantial pruning during the first three weeks after birth, switching from multiple- to single-CF innervation. Previous studies suggested that CF maturation is governed by bidirectional changes of synaptic plasticity. The strengthening of surviving ‘winner’ CFs, which translocate from the PN soma to the dendrite, is thought to be guided by long-term potentiation (LTP), while weakening of to-be-eliminated ‘loser’ CFs, which remain on the soma, was proposed to be due to long-term depression (LTD). However, there are conflicting results from previous studies, whether or not strengthening of winner and weakening of loser CFs during postnatal development is accompanied by changes in short-term plasticity and, thus, whether pre- or postsynaptic forms of LTD and LTP are operational. We, therefore, analyzed the developmental profile of paired-pulse depression (PPD) in ‘weak’ and ‘strong’ CFs in 3- to 21-day old Igsf9-eGFP mice, which allow visual identification of GFP-labeled CFs. We found that in 3-8-day old mice strong CFs are marked by a stronger PPD compared to weak CFs. Surprisingly, PPD of strong CFs eases during maturation, while PPD in weak CFs remains unchanged. This easing of PPD is neither due to changes in presynaptic influx-release coupling nor to an increased saturation of postsynaptic receptors. Thus, our results imply that synaptic contacts of CFs show distinct features of PPD depending on their affiliation to winner or loser CFs and depending on their somatic or dendritic location.